UPAYA MENINGKATKAN HASIL BELAJAR FIQIH MATERI BINATANG YANG HALAL DAN HARAM MELALUI METODE INQUIRY - Septimi Hartati Natalia (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
The purpose of this research is to improve student learning outcomes and student learning activities Animal material that is Halal and Haram by applying the inquiry method to class V students of MIS Darul Ma’arif, Simeulue Regency. This study is a Classroom Action Research (CAR). CAR procedures are in the form of cycles and with stages of planning, action, observation, and reflection. The subjects in this research were all students in class V of MIS Darul Ma'arif, totaling 15 students. The technique of collecting data is by observation and testing. Data were analyzed by descriptive qualitative method. The results of the research showed that: (1) The percentage of completeness of student learning outcomes in a classical on prasiklus was 46.7%. In the first cycle it increased 26.6% to reach 73.3%. In the second cycle there was an increase of 20% to 93.3%. Student learning activities in the first cycle are classified as sufficient with an average of 3.1. Student learning activities in cycle II increased and were classified as good with an average of 3.9. Conclusion: student learning outcomes on halal and illicit animal material can be increased by applying the inquiry method in class V MIS Darul Ma'arif, Simeulue Regency.